Cooking at Home and Adherence to the Mediterranean Diet During the COVID-19 Confinement: The Experience From the Croatian COVIDiet Study - Pfeifer, Danijela; Rešetar, Josip; Gajdoš Kljusurić, Jasenka; Panjkota Krbavčić, Ines; Vranešić Bender, Darija; Rodríguez-Pérez, Celia; Ruíz-López, María Dolores; Šatalić, Zvonimir (Frontiers in Nutrition, 2021)
The primary aims of this study, among others, were to evaluate the changes in dietary behavior among the Croatian adult population during the COVID-19 outbreak and to explore the impact of confinement on cooking habits. The study was based on results from COVIDiet_Int cross-sectional study – a part of COVIDiet project (NCT04449731). A self-administrated online questionnaire was used to assess the frequency of food consumption, eating habits and socio-demographic information. A total number of 4281 participants (80,5% females and 19,4% males) completed the questionnaire. Participants who had higher adherence to the Mediterranean diet were mostly females (88.8%), aged between 20 and 50 years, with the highest level of education (66.3%) and normal BMI (70.6%), who lived in family homes (85.0%) in the continental part of Croatia (74.4%). Major part of participants maintained their dietary behavior the same as before COVID-19 confinement and also had no difficulty in finding certain types of food during the confinement. Additionally, a higher median values of the Mediterranean diet Adherence Screener (MEDAS) score were noted for participants with body mass index values between 18.5 and 24.9 kg/m2. Participants in all residence places increased the cooking frequency during the confinement, which was associated with higher diet quality. According to our findings, Croatian adults exhibited medium adherence to the Mediterranean diet during the COVID-19 confinement. The results suggest that cooking frequency could be positively associated with overall dietary quality, which is of utmost importance in these demanding times.